DNA Hanger: Surface-Minimized Single-Molecule Immunoassay Platform - Seol, Jincheol; Kim, Byungju; Yu, Eui-Sang; Jeong, Cherl hyun; Lee, Jong-Bong (Wiley - V C H Verlag GmbbH & Co., 2025)
A novel single-molecule immunoassay platform, termed DNA Hanger, is developed to address the limitations of conventional surface-based assays. By suspending biotinylated λ-phage DNA across microfabricated quartz barriers, this method enables high-specificity protein detection with minimal nonspecific binding. DNA Hanger significantly reduces background signals, achieving nonspecific binding rates as low as one protein per 236 µm of DNA. Quantification of mNeonGreen-tagged human poly(A)-binding protein C1 (mNG-PABP) and single-molecule fluorescence-linked immunosorbent assay (FLISA) of human tumor necrosis factor α (TNF-α) demonstrates the assay's specificity and sensitivity at the single-molecule level, with a detection limit of 0.90 pM in buffer, 38-fold lower than that of conventional FLISA, and 20.6 pM in 70% fetal bovine serum, an 8-fold improvement. DNA Hanger also enables the detection and quantification of endogenous TNF-α in human serum, highlighting its clinical potential. The DNA Hanger assay eliminates the need for surface blocking and simplifies workflow, resulting in completing the immunoassay process within 1 hour. DNA Hanger offers broad applicability for biomolecular interaction studies and clinical diagnostics.